Mendiagnosis dan Mengatasi Kesalahpahaman dalam Magnetisme: Pendekatan Terpadu Perubahan Konseptual dan Berbasis Simulasi untuk Siswa Sekolah Dasar - Nur Ngazizah; Siska Desy Fatmaryanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study diagnoses persistent misconceptions about magnetism among elementary school students and proposes an evidence-based remediation framework. Using a descriptive qualitative design, data were collected from 29 fifth-grade students through a 16-item multiple-choice diagnostic test developed by the researchers and integrated with a six-point Certainty of Response Index (CRI) scale. The instrument assessed six indicators of magnetism: the definition and properties of magnets, magnetic poles, magnetic and non-magnetic objects, the magnetic field, methods of magnetization, and the utilization of magnets. The results showed that misconceptions were most prominent in abstract concepts, particularly the magnetic field (33.32% of students), and in procedural-to-conceptual transfer areas such as methods of magnetization (29.88% of students). These percentages represent students providing incorrect answers with high confidence, indicating robust misconceptions. The root causes stemmed from intuitive preconceptions and instructional practices that emphasize procedural activities without sufficient conceptual explanation or visualization. To address these issues, the study proposes an integrated pedagogical model combining the Conceptual Change Model (CCM) with interactive digital simulations (e.g., PhET). This dual approach aims to create cognitive conflict, make abstract magnetic phenomena visible, and support the restructuring of students’ mental models toward scientifically accurate conceptions of magnetism.